Risk factors and current state of therapy for anemia after kidney transplantation - Tang, Yan; Guo, Jiayu; Zhou, Jiangqiao; Wan, Zijie; Li, Jinke; Qiu, Tao (Frontiers in Medicine, 2024)
Post-transplant anemia is one of the most common complications in kidney transplant recipients, severely affecting patient prognosis and quality of life, and is an independent predictor of graft kidney loss and patient mortality. However, our clinical understanding and the attention given to post-transplant anemia are currently insufficient. This paper reviews the current status, risk factors, and therapeutic progress in anemia after transplantation in kidney transplant recipients. We recommend that clinical staff pay attention to anemia and its complications in kidney transplant recipients and intervene early for anemia.